Cumplimiento de estándares e indicadores de parto y nacimiento humanizado en el centro de salud tipo C Velasco Ibarra, Machala Ecuador - Reyes Rueda, Elida Yesica; Paccha Tamay, Carmen Liliana; Saraguro Salinas, Sara Margarita (My University, 2022)
Introduction:Childbirth is an extraordinary event in a woman's life, given precisely because it is the culmination of human pregnancy and at the same time the beginning of a new life, which is why special interest is attributed to it at a universal level. Objective:To analyze compliance with humanized childbirth and delivery standards and indicators in the Type C Health Center. Materials and Methods: Observational, descriptive, prospective, cross-sectional study. With a total population of patients treated at the Obstetric Center Service of the "Velasco Ibarra" Institute, in Machala Ecuador from January to December 2020. Results:743 patients had prenatal control with more than 5 sessions, 100% of deliveries were spontaneous with antepartum rupture, without induction and almost all with complete weeks. And in 3, regarding the presentation of delivery, 996 cases were of cephalic presentation. 862 patients did not have companions, but the health group, doctors and nurses and only 125 were allowed to have their partner. As for the position of delivery, 908 were in the lithotomy (gynecological) position, as for analgesia only 267 and none required anesthesia, nor did they require blood, sulfate, iron, or postpartum contraceptives. Conclusions: the inclusion of the humanizing and integral component is required for the conception of childbirth as a natural and physiological process, with the scientific-humanistic combination in achieving care with quality and warmth, where the Ecuadorian woman is the protagonist of her birth process as a a subject of care and not as its object.
Introducción: El parto constituye un acontecimiento extraordinario en la vida de la mujer, dado precisamente, por ser la culminación del embarazo humano y al unísono, el inicio de una nueva vida, razón por la que se le atribuye especial interés a nivel universal. Objetivo:Analizar el cumplimiento de estándares e indicadores de parto y nacimiento humanizado en el Centro de Salud Tipo C.Materiales y Métodos: Estudio observacional, descriptivo, prospectivo, de corte transversal. Con una población total de pacientes atendidas en el Servicio de Centro Obstétrico del Instituto “Velasco Ibarra”, en Machala Ecuador, de enero a diciembre del 2020.Resultados: 743 pacientes tuvieron control prenatal con más de 5 sesiones, el 100% de los partos fue espontaneo, con ruptura anteparto, sin inducción, en su mayoría con las semanas completas. En cuanto a la presentación del parto 996 casos fueron de presentación cefálica. 862 pacientes no tuvieron acompañantes, sino, el grupo sanitario, médicos y enfermeras y solo a 125 se le permitió tener a su pareja. En cuanto a la posición del parto, 908 estuvieron en posición de litotomía (ginecológica), en cuanto a la analgesia, solo 267 y ninguna requirió anestesia, así como tampoco requirieron sangre, sulfato, hierro ni anticonceptivos postparto. Conclusiones: Se precisa la inclusión del componente humanizador e integral para la concepción del parto como un proceso natural y fisiológico, con la combinación científico-humanista en el logro de una atención con calidad y calidez, donde la mujer ecuatoriana protagonice su proceso de parto como un sujeto de cuidado y no como objeto del mismo.
Keywords: PARTO; NACIMIENTO; HUMANIZADO; SALUD